Contract law without foundations toward a republican theory of contract law - Saprai, Prince 1979- (Oxford, United Kingdom Oxford University Press, 2019)
This book advances a theoretical account of contract law, grounded in value pluralism. Arguing against attempts to delineate branches of legal doctrine by reference to single unifying values, the book suggests that a field such as contract law can only be explained and justified by the interaction of a multiplicity of moral values.0In recent times, the philosophy of contract law has been dominated by the 'promise theory', according to which the morality of promise provides a 'blueprint' for the structure, shape, and content that contract law rules and doctrines should take. The promise theory is an example of what this book calls a 'foundationalist' theory, whereby areas of law reflect or are underlain by particular moral principles or sets of such principles. 0By considering contract law from the point of view of its theory, rules and doctrines, and broader political context, the book argues that the promise theory can only ever offer part of the picture. The book claims that 'top-down' theories of contract law such as the promise theory and its bitter rival the economic analysis of law seriously mishandle legal doctrine by ignoring or underplaying the irreducible plurality of values that shape contract law. The book defends the role of this multiplicity of values in forging contract doctrine by developing from the 'ground-up' a radical and distinctly republican reinterpretation of the field. The book encourages readers to move away from a 'top-down' theory of contract law such as the promise theory and instead embrace a distinctly republican approach to contract law that would justify the legal rules and doctrines we find in particular jurisdictions at particular times.
Introduction -- Foundationalism and the promise theory -- The limits of promise -- Republican contract law -- Intent to Contract and trust -- Undue influence and exploitation -- Restraint of trade and freedom -- The penalties rule and compensation -- Mitigation and fairness -- Contract law beyond the state.
Includes bibliographical references and index.
Keywords: Law and ethics. -- Electronic books; Contracts -- Philosophy; Law and ethics; Contracts -- Philosophy